Polyamide film, method for manufacturing the same, laminated film, display
Patent Information
- Application Number
- CN202580023047.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-26
- Publication Date
- 2026-10-27
AI Technical Summary
本发明的聚酰胺膜的耐弯曲性优异,例如即使在反复弯折25万次以上的情况下也不易变形,因此在用作折叠型显示器用的表面保护膜的情况下,能够有效地抑制折叠部分处的图像的紊乱。另外,本发明的聚酰胺膜的透明性优异,因此适合用作显示器用的表面保护膜。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to polyamide films suitable for use as surface protective films. Background Technology
[0002] To protect the displays of mobile devices and other mobile terminals from damage, impacts, etc., a surface protective film is used.
[0003] In recent years, mobile terminals equipped with flexible displays or foldable displays have been developed, as well as surface protective films for foldable displays (for example, see Patent Document 1).
[0004] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2023-061931 Summary of the Invention
[0005] The technical problem that the invention aims to solve The protective film used in foldable displays needs to withstand repeated bending, but the bending resistance of previous protective films was insufficient. Therefore, there is a need to develop a protective film with excellent bending resistance.
[0006] The present invention was made in view of the above-mentioned problems, and its object is to provide a polyamide film with improved bending resistance, a method for manufacturing the same, a laminated film having the polyamide film, and a display.
[0007] Technical solutions for solving technical problems The present invention provides an invention in the following manner.
[0008] <1> A polyamide film comprising a semi-aromatic polyamide, The polyamide film has a refractive index of less than 1.600 in the length direction and / or width direction, and the difference between the refractive index in the length direction and the refractive index in the width direction is greater than 0.030.
[0009] <2> According to the polyamide film described in <1>, the 0.2% offset strain (Japanese: 0.2% endurance) of the polyamide film in the length direction and / or width direction is 2.30% or more.
[0010] <3> According to <1> or <2>, the polyamide film has a haze of less than 1.0%.
[0011] <4> The polyamide film according to any one of <1> to <3>, wherein the total light transmittance of the polyamide film is 85.0% or more.
[0012] <5> The polyamide film according to any one of <1> to <4>, wherein the thickness of the polyamide film is 100. m Below m.
[0013] <6> The laminated film formed by laminating the polyamide film of any one of <1> to <5> with a hard coating.
[0014] <7> A display having a polyamide film as described in any one of <1> to <5>.
[0015] <8> A display having the laminated film described in <6> The display is configured with the hard coating of the laminated film on the outside.
[0016] <9> The method for manufacturing the polyamide film according to any one of <1> to <5>, The manufacturing method includes a stretching process, wherein an unstretched film containing semi-aromatic polyamide is uniaxially stretched along the length or width direction at a stretching ratio of 1.5 to 4.0 times.
[0017] <10> According to the method for manufacturing polyamide film as described in <9>, no heat-fixing treatment and relaxation treatment are performed after the stretching process.
[0018] <11> According to the method for manufacturing polyamide film as described in <9> or <10>, the heat of crystallization of the unstretched film is 20 J / g or higher.
[0019] Invention Effects The polyamide film of the present invention exhibits excellent bending resistance; for example, it is not easily deformed even after being repeatedly bent more than 250,000 times. Therefore, when used as a surface protective film for foldable displays, it can effectively suppress image distortion at the folded portion. Furthermore, the polyamide film of the present invention has excellent transparency, making it suitable for use as a surface protective film for displays. Detailed Implementation
[0020] 1. Polyamide film The polyamide film of the present invention comprises a semi-aromatic polyamide, having a refractive index of 1.600 or less in the length direction and / or width direction, and the difference between the refractive index in the length direction and the refractive index in the width direction is 0.030 or more. The polyamide film of the present invention will now be described in detail.
[0021] Semi-aromatic polyamides The semi-aromatic polyamide constituting the polyamide film of the present invention is composed of at least an aromatic dicarboxylic acid component and an aliphatic diamine component.
[0022] There are no particular limitations on the aromatic dicarboxylic acid components; examples include terephthalic acid, isophthalic acid, and naphthalenedicarboxylic acid (1,2-form, 1,3-form, 1,4-form, 1,5-form, 1,6-form, 1,7-form, 1,8-form, 2,3-form, 2,6-form, and 2,7-form). One or more of these can be used. Terephthalic acid is preferred.
[0023] From the viewpoint of improving the heat resistance and reducing the water absorption of polyamide films, the aromatic dicarboxylic acid component preferably contains 60 mol% or more of terephthalic acid, more preferably 70 mol% or more, further preferably 85 mol% or more, even more preferably 90 mol% or more, and particularly preferably 100 mol% of terephthalic acid.
[0024] Semi-aromatic polyamides may contain dicarboxylic acid components other than aromatic dicarboxylic acid components without impairing the effects of the present invention, but preferably do not contain other dicarboxylic acid components. Examples of other dicarboxylic acids include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, dodecanoic acid, tetradecanoic acid, and octadecanoic acid. One or more of these may be used.
[0025] There are no particular limitations on the aliphatic diamine component. Preferably, it is an aliphatic diamine with 6 to 12 carbon atoms as the main component; more preferably, it is an aliphatic diamine with 9 to 12 carbon atoms as the main component; and even more preferably, it is an aliphatic diamine with 9 or 10 carbon atoms as the main component. It should be noted that "as a main component" means containing 50 mol% or more.
[0026] From the viewpoint of balancing the heat resistance and productivity of polyamide films, the content of aliphatic diamines with 6 to 12 carbon atoms in the aliphatic diamine component is preferably 60 mol% or more, more preferably 75 mol% or more, even more preferably 90 mol% or more, and particularly preferably 100 mol%. One type of aliphatic diamine with 6 to 12 carbon atoms may be used, or two or more types may be used in combination. It should be noted that when two or more types are used in combination, the content is the sum of their amounts.
[0027] Examples of aliphatic diamines with 6 to 12 carbon atoms include: straight-chain aliphatic diamines such as 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, and 1,12-dodecanediamine; and branched-chain aliphatic diamines such as 2-methyl-1,8-octanediamine, 4-methyl-1,8-octanediamine, 5-methyl-1,9-nonanediamine, 2,2,4- / 2,4,4-trimethyl-1,6-hexanediamine, 2-methyl-1,5-pentanediamine, 2-methyl-1,6-hexanediamine, and 2-methyl-1,7-heptanediamine.
[0028] Examples of aliphatic diamines other than those with 6 to 12 carbon atoms include linear aliphatic diamines such as 1,4-butanediamine and 1,5-pentanediamine.
[0029] Semi-aromatic polyamides may contain diamine components other than aliphatic diamines without impairing the effects of the present invention, but preferably not. Examples of other diamine components include alicyclic diamines such as isophorone diamine, norbornene dimethylamine, and tricyclodecane dimethylamine; and aromatic diamines such as m-phenylenediamine, p-phenylenediamine, m-phenylenediamine, and p-phenylenediamine. One or more of these components may be used.
[0030] The semi-aromatic polyamide may be copolymerized with one or more species without impairing the effects of the present invention. e -Caprolactam, g -Hemprolactam, or -octinolamine and oh - Lactams such as dodecyl lactam.
[0031] The types and copolymerization ratios of the monomers constituting the semi-aromatic polyamide are preferably selected such that the resulting semi-aromatic polyamide has a melting point (Tm) of 270–350°C and a glass transition temperature (Tg) of 100–135°C. Tm is more preferably 280–330°C, and even more preferably 280–310°C. Tg is more preferably 110–130°C, and even more preferably 120–125°C. By achieving Tm and Tg within the above ranges, the semi-aromatic polyamide exhibits sufficient heat resistance and effectively suppresses thermal decomposition during processing into a film.
[0032] Semi-aromatic polyamides may contain end-capping agents and polymerization catalysts. Examples of end-capping agents include acetic acid, lauric acid, benzoic acid, octylamine, cyclohexylamine, and aniline. Examples of polymerization catalysts include phosphoric acid, phosphorous acid, hypophosphorous acid, and their salts.
[0033] There are no particular limitations on the intrinsic viscosity of the semi-aromatic polyamide. From the viewpoint of producing polyamide films with excellent mechanical strength with good productivity, it is preferably 0.8 to 2.0 dL / g, more preferably 0.9 to 1.8 dL / g, even more preferably 1.0 to 1.5 dL / g, and even more preferably 1.0 to 1.3 dL / g.
[0034] <Method for manufacturing semi-aromatic polyamides> Semi-aromatic polyamides can be manufactured using methods known as methods for manufacturing crystalline polyamides. Examples include: solution polymerization or interfacial polymerization using acyl chloride and diamine components as raw materials (Method A); methods using dicarboxylic acid and diamine components as raw materials to obtain oligomers, and then increasing the molecular weight of the obtained oligomers through melt polymerization or solid-state polymerization (Method B); methods using dicarboxylic acid and diamine components as raw materials to obtain a broken mixture of salt and oligomers, and then subjecting the broken mixture to solid-state polymerization (Method C); methods using dicarboxylic acid and diamine components as raw materials to obtain a salt, and then subjecting the salt to solid-state polymerization (Method D), etc. Among these methods, Methods C and D are preferred, and Method D is more preferred. Compared to Method B, Methods C and D can generate a broken mixture of salt and oligomers or salt at low temperatures, and the generation of the broken mixture of salt and oligomers or salt does not require a large amount of water. Therefore, the formation of gel-like substances and fisheyes can be reduced.
[0035] In method B, for example, nylon salt prepared by mixing a diamine component, a dicarboxylic acid component, and a polymerization catalyst is heated and polymerized at 200–250°C to obtain oligomers. The intrinsic viscosity of the oligomer is preferably 0.1–0.6 dL / g. Setting the intrinsic viscosity of the oligomer within this range has the advantage that the molar balance between the carboxyl groups in the dicarboxylic acid component and the amino groups in the diamine component is not disrupted during subsequent melt polymerization or solid-state polymerization, thus accelerating the polymerization rate. When the intrinsic viscosity of the oligomer is less than 0.1 dL / g, the polymerization time sometimes becomes longer, resulting in poor productivity. On the other hand, when the intrinsic viscosity of the oligomer exceeds 0.6 dL / g, the resulting semi-aromatic polyamide may sometimes become discolored.
[0036] Solid-state polymerization of oligomers is preferably carried out under reduced pressure or with a flow of inert gas. Furthermore, the solid-state polymerization temperature is preferably 200–280°C. By setting the solid-state polymerization temperature within this range, coloring and gelation of the resulting semi-aromatic polyamide can be suppressed. When the solid-state polymerization temperature is below 200°C, the polymerization time sometimes becomes longer, resulting in poor productivity. On the other hand, when the solid-state polymerization temperature exceeds 280°C, the resulting semi-aromatic polyamide may sometimes color or gel.
[0037] Melt polymerization of oligomers is preferably carried out below 350°C. When the polymerization temperature exceeds 350°C, it can sometimes promote the decomposition and thermal degradation of semi-aromatic polyamides. Therefore, polyamide films obtained from such semi-aromatic polyamides sometimes have poor strength and appearance. It should be noted that the above-mentioned melt polymerization also includes melt polymerization using a melt extruder.
[0038] In method C, for example, a suspension containing a molten aliphatic diamine and a solid aromatic dicarboxylic acid is stirred and mixed to obtain a mixture. Then, in this mixture, at a temperature below the melting point of the final semi-aromatic polyamide, a salt formation reaction based on the reaction between the aromatic dicarboxylic acid and the aliphatic diamine, and an oligomer formation reaction based on the polymerization of the formed salt are carried out to obtain a mixture of salt and oligomers. In this case, crushing can be performed while reacting, or it can be temporarily removed after the reaction and then crushed. Then, the obtained reactants are subjected to solid-state polymerization at a temperature below the melting point of the final semi-aromatic polyamide to increase the molecular weight to a specified molecular weight, thereby obtaining a semi-aromatic polyamide. Solid-state polymerization is preferably carried out at a polymerization temperature of 180–270°C and a reaction time of 0.5–10 hours in a stream of inert gas such as nitrogen.
[0039] In method D, for example, an aromatic dicarboxylic acid powder is preheated to a temperature above the melting point of the aliphatic diamine but below the melting point of the aromatic dicarboxylic acid. At this temperature, the aliphatic diamine is added to the aromatic dicarboxylic acid powder while maintaining its powder state by essentially eliminating water, thus obtaining a salt. The resulting salt is then subjected to solid-state polymerization at a temperature below the melting point of the ultimately formed semi-aromatic polyamide to increase its molecular weight to a specified value, yielding the semi-aromatic polyamide. Solid-state polymerization is preferably carried out at a polymerization temperature of 180–270°C and a reaction time of 0.5–10 hours in a stream of inert gas such as nitrogen.
[0040] Semi-aromatic polyamides can be virgin semi-aromatic polyamides, or they can be non-standard films obtained during the manufacture of semi-aromatic polyamide films, mixtures of scrap materials generated as waste, or substances prepared by adding virgin semi-aromatic polyamides to such mixtures. Their mixing can be carried out using known methods such as dry mixing with known apparatus or melt mixing using a single-shaft or bi-shaft extruder.
[0041] Semi-aromatic polyamides can be commercially available. Examples of commercially available semi-aromatic polyamides include: Genestar (registered trademark) manufactured by Kuraray Corporation, XecoT (registered trademark) manufactured by Uniqlo Corporation, Reny (registered trademark) manufactured by Mitsubishi Engineering Plastics Co., Ltd., Arlen (registered trademark) manufactured by Mitsui Chemicals Co., Ltd., and Ultramid (registered trademark) manufactured by BASF Corporation.
[0042] <Characteristics of Polyamide Films> The polyamide film of the present invention has a refractive index of 1.600 or less in its length direction (mechanical flow direction, hereinafter also referred to as the "MD direction") and / or its width direction (direction orthogonal to the length direction, hereinafter also referred to as the "TD direction"), preferably 1.580 or less, and more preferably 1.570 or less. The lower limit of the refractive index is not particularly limited, for example, it is 1.500 or more. Furthermore, the polyamide film of the present invention preferably has a refractive index in either the MD direction or the TD direction within the above-mentioned range, and the other refractive index exceeds 1.600, more preferably 1.610 or more. The upper limit of the other refractive index is not particularly limited, for example, it is 1.700 or less.
[0043] When the refractive index in the MD direction and / or TD direction is below 1.600, the semi-aromatic polyamide is highly oriented along the planar direction. Therefore, when the polyamide film is repeatedly folded, there is less deformation, and it is not easy to generate cracks or break. Thus, it can maintain the visibility of the display well.
[0044] Furthermore, the difference between the refractive index in the MD direction and the refractive index in the TD direction of the polyamide film of the present invention is 0.030 or more, preferably 0.035 or more, more preferably 0.040 or more, even more preferably 0.045 or more, and particularly preferably 0.050 or more. There is no particular limitation on the upper limit of the refractive index difference, for example, it is 0.500 or less.
[0045] When the difference between the refractive index in the MD direction and the refractive index in the TD direction is greater than 0.030, the semi-aromatic polyamide is highly oriented along the uniaxial direction. Therefore, when the polyamide film is repeatedly folded, there is less deformation and it is less prone to cracking.
[0046] From the viewpoint of further improving bending resistance, the 0.2% offset strain of the polyamide film in the MD direction and / or TD direction of the present invention is preferably 2.30% or more, more preferably 2.40% or more, and even more preferably 2.50% or more. There is no particular limitation on the upper limit of the 0.2% offset strain, for example, it is 3.50% or less. The 0.2% offset strain refers to a value used as a substitute for the yield point regardless of whether a yield point appears in the stress-strain curve, and is used as an indicator of the elastic region. In the present invention, the 0.2% offset strain is a value calculated by obtaining the stress-strain curve using a tensile testing machine and setting the strain to 0.2% using Autograph software.
[0047] From the viewpoint of the transparency and visibility requirements of surface protective films for displays, the haze of the polyamide film of the present invention is preferably 1.0% or less, more preferably 0.5% or less, further preferably 0.3% or less, and even more preferably 0.2% or less. In the present invention, the haze is a value measured according to JIS K7136:2000 (Method for determining the haze of transparent materials in plastics).
[0048] From the viewpoint of visibility requirements for surface protective films used in displays, the total light transmittance of the polyamide film of the present invention is preferably 85.0% or more, more preferably 90.0% or more. In the present invention, the total light transmittance is a value measured according to JIS K 7361-1:1997 (Plastics - Test method for total light transmittance of transparent materials - Part 1: Single beam method).
[0049] The thickness of the polyamide film of the present invention is not particularly limited, but from the viewpoint of suppressing the easy retention of bending marks caused by repeated bending at the folded portion, a thickness of 100 mm is preferred. m Below m, more preferably 75 m Below m, more preferably 50 m Below m.
[0050] 2. Manufacturing method of polyamide film The manufacturing method of the polyamide film of the present invention is not particularly limited. For example, by adjusting the crystallization state and stretching conditions of the unstretched film, the polyamide film of the present invention having the above-mentioned characteristics can be obtained.
[0051] The polyamide film of the present invention can be manufactured, for example, by uniaxially stretching an unstretched film containing a semi-aromatic polyamide at a stretch ratio of 1.5 to 4.0 times along the MD or TD direction.
[0052] Unstretched membranes contain at least semi-aromatic polyamides. To improve various membrane properties, they may contain lubricants, pigments and dyes such as titanium dioxide, anti-staining agents, heat stabilizers, hindered phenols, phosphate esters, phosphites and other antioxidants, benzotriazole compounds and other weather-resistant modifiers, bromine-based and phosphorus-based flame retardants, plasticizers, release agents, talc and other reinforcing agents, modifiers, antistatic agents, ultraviolet absorbers, anti-fogging agents, and various resins and other additives. One or more of these additives may be used. Alternatively, resin layers containing the above additives may be laminated onto unstretched or stretched membranes.
[0053] The resin constituting the above-mentioned resin layer is not particularly limited, and various resins can be used. Examples of resins include polyamide resins, polyester resins, polyurethane resins, acrylic resins, and epoxy resins. Among these, polyamide resins, polyester resins, polyurethane resins, and acrylic resins are preferred from the viewpoint of excellent adhesion to the hard coating.
[0054] Examples of lubricants that provide good sliding properties include inorganic particles such as silica, alumina, titanium dioxide, calcium carbonate, kaolin, and barium sulfate; and organic particles such as acrylic resin particles, melamine resin particles, silicone resin particles, and cross-linked polystyrene particles. The average particle size of the lubricant is preferably 0.03 to 5.0 mm. m m.
[0055] The content of lubricant can be adjusted appropriately according to the frictional properties, optical properties, and other required properties of the polyamide film. In order to make the haze of the polyamide film less than 1.0%, it is preferable to set it to less than 0.2% by mass when the polyamide film is a single layer.
[0056] In the case where the polyamide film of the present invention is a multilayer film having multiple films stacked together, it is preferable to control the content of lubricant in the entire multilayer film. For example, a multilayer film can be obtained by stacking a thin film containing a high concentration of lubricant with a film without lubricant.
[0057] Various methods can be used to make the unstretched film contain the above-mentioned additives. The following methods are representative examples.
[0058] (A) Method for adding additives during the polymerization of semi-aromatic polyamides (B) Masterbatch method for preparing melt-blended granules by directly adding additives to semi-aromatic polyamides. (C) A method in which additives are directly added to semi-aromatic polyamides during membrane fabrication, and melt-blending is performed using an extruder. (D) A method of directly adding additives to the extruder during film production and performing melt mixing. Examples of methods for laminating a resin layer containing the above-mentioned additives onto a membrane containing a semi-aromatic polyamide include: coating a solution or aqueous dispersion of various solvents forming the resin layer onto the membrane containing the semi-aromatic polyamide; thermally melting the composition forming the resin layer and extruding it onto the membrane containing the semi-aromatic polyamide; and forming a resin layer on the outermost layer when extruding a multilayer membrane containing the semi-aromatic polyamide, but are not limited to these methods.
[0059] The heat of crystallization of the unstretched film is preferably 20 J / g or more, more preferably 25 J / g or more. When the heat of crystallization of the unstretched film is less than 20 J / g, crystallization is underway, and stretching may sometimes be impossible due to multiple cuts. Higher stretching forces are required in the initial stages of stretching, making it difficult to obtain a stretched film with uniform thickness. Furthermore, even when a stretched film is obtained, haze may increase, resulting in poor transparency. There is no particular upper limit to the heat of crystallization, for example, it can be 30 J / g or less.
[0060] Unstretched films with a heat of crystallization of 20 J / g or higher can be manufactured, for example, by melting and mixing semi-aromatic polyamide in an extruder at a temperature of 280–340°C, extruding it into sheets using a die such as a T-die, and then pressing the sheets onto a cooling medium (e.g., a roller) at a temperature adjusted to 20–40°C for cooling. When the temperature of the cooling medium exceeds 40°C, the heat of crystallization of the resulting unstretched film tends to be less than 20 J / g, which can easily lead to the aforementioned problems after stretching.
[0061] Then, the unstretched film is stretched, and through stretching, the semi-aromatic polyamide is highly oriented. There are no particular limitations on the stretching method; examples include roller stretching, tenter frame stretching, and tubular stretching.
[0062] The stretching is preferably performed uniaxially along the MD or TD direction. Furthermore, the direction of uniaxial stretching is preferably the direction in which the polyamide film is repeatedly bent. By performing uniaxial stretching along this direction, the semi-aromatic polyamide is highly oriented along the stretching direction, resulting in the polyamide film of the present invention having the above-described characteristics.
[0063] From the viewpoint of easily manufacturing the polyamide film of the present invention having the above-mentioned characteristics, the stretching ratio during uniaxial stretching is preferably 1.5 to 4.0 times, more preferably 2.0 to 4.0 times, and even more preferably 2.4 to 3.8 times.
[0064] The stretching can be biaxial along the MD direction and the TD direction. When biaxial stretching is performed, from the viewpoint of obtaining the polyamide film of the present invention with the above-described characteristics, it is necessary to adjust the stretching ratio of either direction to 1.2 times or less. The other stretching ratio is preferably 1.5 to 4.0 times, more preferably 2.0 to 4.0 times, and even more preferably 2.4 to 3.8 times.
[0065] From the viewpoint of stably manufacturing polyamide films by suppressing film breakage, and from the viewpoint of suppressing stretching spots and highly oriented semi-aromatic polyamides along the stretching direction, the stretching temperature is preferably within ±20°C of the glass transition temperature (Tg) of the semi-aromatic polyamide, and more preferably within ±10°C of Tg.
[0066] Heat setting can also be performed after the stretching process. However, heat setting can sometimes mitigate the orientation of the semi-aromatic polyamide, so it is preferable not to perform heat setting. The temperature of the heat setting is preferably below 250°C, more preferably below 200°C, and even more preferably below Tg. The time of the heat setting is not particularly limited, for example, 20 to 120 seconds.
[0067] As a method of heat fixation, known methods include blowing hot air, irradiating with infrared rays, and irradiating with microwaves.
[0068] Relaxation treatment can also be performed after heat setting. However, sometimes the orientation of the semi-aromatic polyamide is moderated and the 0.2% offset strain is reduced due to relaxation treatment, so it is preferable not to perform relaxation treatment. The relaxation rate when relaxation treatment is performed is, for example, 2% or less.
[0069] The resulting polyamide film can be made into a single sheet or into a roll by winding it onto a take-up roller. From the viewpoint of productivity for various applications, it is preferable to make it into a roll. When made into a roll, it can be cut to the required width.
[0070] Polyamide films can be single-layer films composed of a single layer or multilayer structures composed of two or more layers. In the case of multilayer structures, for example, in the case of a two-layer film, any one layer contains a lubricant; in the case of a three-layer film, each of the layers located on the two surfaces contains a lubricant. The type and amount of lubricant contained can be designed independently. By adopting such a multilayer structure, the surface roughness of each surface of the polyamide film can be controlled independently.
[0071] To ensure good adhesion to other raw materials, the surface of the polyamide film can be treated with corona treatment, plasma treatment, acid treatment, and flame treatment.
[0072] 3. Laminated film The laminated film of the present invention is formed by laminating the polyamide film of the present invention with a hard coating layer.
[0073] Examples of resins that form hard coatings include acrylic resins, siloxane resins, inorganic hybrid resins, polyurethane acrylate resins, polyester acrylate resins, and epoxy resins. One or more of these resins may be used. Furthermore, the hard coating may contain particles such as inorganic and organic fillers.
[0074] There is no particular limitation on the thickness of the hard coating, but from the viewpoints of surface protection and suppressing curling and improving the operability of the film, a thickness of 1 to 50 mm is preferred. m m, more preferably 1 to 40 m m, more preferably 3-20 m m.
[0075] Hard coatings can be formed, for example, by applying a resin composition to form a hard coating using a coating machine such as a Mayer rod, gravure coating, die coating machine, or blade coating machine, and then curing it by irradiation with energy rays such as ultraviolet rays and electron beams or by heating.
[0076] 4. Monitor Displays, for example, are display devices in mobile terminal devices. Specifically, examples include LCDs, organic EL displays, inorganic EL displays, LEDs, and FEDs. Organic EL displays may include, for example, an organic EL layer, a phase retardation plate for improving image quality, and a polarizer. The organic EL layer may include electrodes / electron transport layers / light-emitting layers / hole transport layers / transparent electrodes. Additionally, mobile terminal devices may also have touchscreens.
[0077] The display of the present invention has the polyamide film or laminated film of the present invention. When the display of the present invention has the laminated film of the present invention, it is configured such that the hard coating layer of the laminated film is on the outside.
[0078] The display of the present invention is preferably a flexible display or a foldable display, more preferably a foldable display. A foldable display refers to a single continuous display that can be folded into two or more displays. The polyamide film or laminated film of the present invention can be disposed on the outer side or the inner side of the foldable display.
[0079] The display of the present invention has the polyamide film of the present invention with excellent bending resistance, so that even if it is repeatedly bent more than 250,000 times, and even more than 300,000 times, the image is not easily disordered in the folded part.
[0080] Example The present invention will be specifically described below through embodiments, but the present invention is not limited to these embodiments.
[0081] 1. Evaluation Methods (1) Intrinsic viscosity In concentrated sulfuric acid at 30°C, the intrinsic viscosity of the resin at concentrations of 0.05, 0.1, 0.2, and 0.4 g / dL is calculated using the following formula. or (inh), and the value obtained by extrapolating it to concentration 0 is taken as the intrinsic viscosity. or ].
[0082] or inh=[ln(t1 / t0)] / c In the formula, or inh represents the intrinsic viscosity (dL / g), t0 represents the solvent flow time (seconds), t1 represents the resin solution flow time (seconds), and c represents the resin concentration in the solution (g / dL). (2) Melting point, glass transition temperature, heat of crystallization Using a differential scanning calorimeter (Perkin Elmer, DSC-7), the fabricated film was heated from 20°C to 350°C at a rate of 10°C / min under a nitrogen atmosphere and held for 5 minutes (first scan). It was then cooled from 350°C to 20°C at a rate of 100°C / min and held for 5 minutes. The glass transition temperature during the second scan (heating from 20°C to 350°C at a rate of 10°C / min) was taken as Tg, and the peak temperature of the crystallization melting peak was taken as the melting point Tm. Similarly, the integral value of the heated crystallization peak observed in the second scan was taken as the heat of crystallization.
[0083] (3) Refractive index An Abbe refractometer manufactured by ATAGO was used, with a polarizer-equipped analyzer mounted on the eyepiece side. Monochromatic NaD line was used as the light source, and diiodomethane was used as the mounting solution. The refractive indices of the film in the MD and TD directions were measured at 23°C. Samples were taken from the center of the entire width of the fabricated film. For MD direction refractive index measurements, a strip measuring 40 mm in the MD direction and 8.0 mm in the TD direction was taken; for TD direction refractive index measurements, a strip measuring 40 mm in the TD direction and 8.0 mm in the MD direction was taken. The average value of the measurements for n=5 was taken as the refractive index.
[0084] (4) 0.2% offset strain After conditioning the fabricated membrane at 23°C and 50%RH for one day, test pieces (10mm wide × 100mm long) were cut out. Tensile tests were then conducted using a tensile testing machine (Shimadzu AUTOGRAPH AG-X Plus) at a tensile speed of 100mm / min. Based on the obtained stress-strain curve, the slope of an approximate line with a strain range of 0.2% to 0.5% in the stress-strain curve was calculated using Shimadzu's Autograph software TRAPEZIUM X. The strain at the intersection of this line with the stress-strain curve, which is a parallel line shifted by a strain of 0.2%, was taken as the 0.2% offset strain.
[0085] (5) Haze and total transmittance The haze of the fabricated film was measured using a haze meter (NDH 2000) manufactured by Nippon Denshoku Co., Ltd., in accordance with JIS K7136:2000 (Method for determining haze of transparent plastics). Furthermore, the total transmittance of the fabricated film was measured using the same haze meter, in accordance with JIS K 7361-1:1997 (Test method for total transmittance of transparent plastics - Part 1: Single beam method).
[0086] (6) Bending resistance of the membrane The prepared membrane was cut into 30×100mm rectangles to create samples. The short sides of each sample were fixed to a durability testing machine (manufactured by Yuasa System Machinery Co., Ltd., DLDMLH-FS), with a minimum interval of 1.5mm between opposing edges. The samples were subjected to 300,000 bends at a bending radius of 1.0mm, bending angles of 0–180°, and a test speed of 60 cycles / minute. The presence of cracks, breaks, creases, and whitening at the bends was then visually inspected, and the bending resistance was evaluated according to the following criteria. It should be noted that, practically, evaluation criteria A or B is required, with evaluation criterion A being particularly preferred.
[0087] [Evaluation Criteria] A: After 300,000 bending cycles, the bent part showed no cracks or breaks, and no creases or whitening occurred.
[0088] B: After 300,000 bending cycles, there were no cracks or breaks in the bent part. Although creases remained, no whitening occurred.
[0089] C: After 200,000 bends, the bent part showed no cracks or breaks, and no creases or whitening occurred. However, after 300,000 bends, the bent part showed no cracks or breaks, but creases remained and whitening occurred.
[0090] D: After 200,000 bends, no cracks or breaks were produced in the bent part, but residual creases and whitening occurred.
[0091] E: After 200,000 bends, cracks or breaks appear in the bent part, and creases remain, resulting in whitening.
[0092] 2.Raw materials (1) Resin semi-aromatic polyamide Use the semi-aromatic polyamide obtained in the manufacturing example below.
[0093] Manufacturing example Terephthalic acid (TA), 1,9-nonanediamine (NDA), 2-methyl-1,8-octanediamine (MODA) and benzoic acid (BA) (TA / BA / NDA / MODA = 99 / 2 / 80 / 20 (molar ratio)) were added to the reactor. Sodium hypophosphite monohydrate (0.1% by mass relative to the total amount of the above polyamide raw materials) and distilled water were then added to the reactor for nitrogen replacement.
[0094] After stirring the contents of the reactor at 100°C for 30 minutes, the internal temperature was raised to 210°C over a period of 2 hours. At this point, the internal pressure of the reactor reached 2.12 MPa (22 kg / cm²). 2 After continuing the reaction under these conditions for 1 hour, the temperature was raised to 230°C and then maintained at 230°C for 2 hours, while slowly releasing the water vapor, and maintaining the pressure at 2.12 MPa (22 kg / cm²). 2 The reaction proceeded simultaneously. Then, over a period of 30 minutes, the pressure was reduced to 0.98 MPa (10 kg / cm²). 2 The mixture was further reacted for 1 hour to obtain the prepolymer. The prepolymer was dried at 100°C under reduced pressure for 12 hours and then pulverized to a size of less than 2 mm.
[0095] Next, the pulverized prepolymer was subjected to solid-state polymerization at a temperature of 230°C and a pressure of 13.3 Pa (0.1 mmHg) for 10 hours to obtain the polymer. The polymer was fed into a twin-screw extruder (manufactured by Nippon Steel Works, TEX44C), where it was melt-mixed and extruded at a barrel temperature of 320°C. After cooling and cutting, it was produced into semi-aromatic polyamide granules.
[0096] The melting point, glass transition temperature, and intrinsic viscosity of the semi-aromatic polyamide and the polyethylene terephthalate used in Comparative Example 4 are shown in Table 1.
[0097] [Table 1]
[0098] (2) Particles Use a masterbatch containing 2% by mass of silica, manufactured by the following method.
[0099] 98 parts by weight of the manufactured semi-aromatic polyamide and silica particles (manufactured by Fuji Silysia Chemical Co., Ltd., SYLYSIA 310P, average particle size 2.7 mm) were mixed. m 2 parts by mass of m were melt-blended to produce a masterbatch containing 2% by mass of silica particles.
[0100] (3) Hindered phenolic heat stabilizers Use GA: 3,9-bis[2-{3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane (manufactured by Sumitomo Chemical Co., Ltd., SUMILIZER GA-80, thermal decomposition temperature 392°C).
[0101] Example 1 The semi-aromatic polyamide and GA were mixed at a ratio of 0.2 parts by mass relative to 100 parts by mass of the semi-aromatic polyamide. The mixture was melt-mixed in an extruder at 320°C, then extruded into sheets through a T-die set to 320°C. The sheets were then electrostatically bonded to cooling rollers with a surface temperature set to 40°C and cooled to obtain a sheet with a thickness of 190 mm. m m is an unoriented, unstretched membrane.
[0102] The obtained unstretched film was cut into 12×12cm squares and placed in an intermittent biaxial stretching machine (Bruckner Maschinenbau, KARO IV) for uniaxial stretching (TD direction) to obtain a thickness of 50. m The polyamide film is m thick. The stretching conditions are preheating and stretching temperature of 115°C and stretching ratio of 3.4. The TD direction is orthogonal to the flow direction (MD direction) during the manufacturing of the unstretched film.
[0103] Example 2 The stretch ratio was changed to 2.4 times, and the polyamide film was otherwise obtained by the same method as in Example 1.
[0104] Example 3 The unstretched film, manufactured using the same method as in Example 1, was uniaxially stretched (MD direction) to 2.4 times its original size using a longitudinal stretching roller heated to 115°C, yielding a thickness of 50 mm. m m polyamide film.
[0105] Examples 4, 5, 8, 9, and 13 The stretching ratio, stretching temperature, and film thickness were changed to those recorded in Table 2. Otherwise, the polyamide film was obtained by the same method as in Example 3.
[0106] Example 6 The unstretched film, manufactured using the same method as in Example 1, was stretched (MD direction) to 2.4 times its original length using a longitudinal stretching roller heated to 115°C to obtain a film. The resulting film was cut into 12×12cm squares and stretched along the TD direction using an intermittent biaxial stretching machine (Bruckner Maschinenbau, KARO IV) to obtain a thickness of 50 mm. m The polyamide film is m in size. The stretching conditions in the TD direction are: preheating and stretching temperature 115℃, stretching ratio 1.1 times.
[0107] Example 7 The stretching ratio in the TD direction was changed to 1.2 times, and otherwise, a polyamide film was obtained by the same method as in Example 6.
[0108] Example 10 The polyamide film manufactured by the same method as in Example 5 was further heat-treated at 250°C for 50 seconds to obtain a polyamide film that had been heat-fixed after uniaxial stretching.
[0109] Example 11 The semi-aromatic polyamide, GA and masterbatch were mixed in such a manner that, relative to 100 parts by weight of semi-aromatic polyamide, 0.2 parts by weight of GA and 0.1 parts by weight of silica, a polyamide film was obtained by the same method as in Example 1.
[0110] Example 12 The polyamide film manufactured by the same method as in Example 11 was further heat-treated at 250°C for 50 seconds to obtain a polyamide film that had been heat-fixed after uniaxial stretching.
[0111] Comparative Example 1 The stretch ratio was changed to that recorded in Table 3, and the polyamide film was obtained by the same method as in Example 6.
[0112] Comparative Example 2 An unstretched film manufactured using the same method as in Example 1 was stretched (MD direction) to 2.5 times its original length using a longitudinal stretching roller heated to 115°C to obtain a film. The resulting film was cut into 12×12cm squares and stretched along the TD direction using an intermittent biaxial stretching machine (manufactured by Bruckner Maschinenbau, KARO IV). The stretching conditions in the TD direction were a preheating and stretching temperature of 115°C and a stretching ratio of 3.4 times.
[0113] After stretching, it is heat-fixed at 275℃ for 10 seconds, and then relaxed at a relaxation rate of 3.0% in the MD direction and 2.2% in the TD direction to obtain a thickness of 50. m m polyamide film.
[0114] Comparative Example 3 The unstretched film, manufactured using the same method as in Example 1, was cut into 12×12cm squares and placed in an intermittent biaxial stretching machine (manufactured by Bruckner Maschinenbau, KARO IV) for simultaneous biaxial stretching. The stretching conditions were: preheating and stretching temperature 115°C, stretch ratio of 3.0 times in the MD direction, and stretch ratio of 3.3 times in the TD direction.
[0115] After stretching, it is heat-fixed at 275℃ for 10 seconds, and then relaxed at a relaxation rate of 1.0% in the MD direction and 8.0% in the TD direction to obtain a thickness of 25. m m polyamide film.
[0116] Comparative Example 4 Polyethylene terephthalate granules were extruded into sheets through a T-die set to 280°C. These sheets were then electrostatically bonded to a cooling roller with a surface temperature set to 40°C and cooled to obtain a sheet with a thickness of 180 mm. m An unoriented, unstretched film of m thickness was obtained. The resulting unstretched film was stretched (MD direction) to 3.3 times its original size using a longitudinal stretching roll heated to 80°C to obtain a thickness of 50 μm. m m polyester film.
[0117] Comparative Example 5 An attempt was made to manufacture a polyamide film using the same method as in Example 1, except that the stretch ratio was changed to 4.2 times. However, due to the excessive stretch ratio, the film broke and the polyamide film could not be manufactured.
[0118] The composition of the particles used, the manufacturing conditions of the membrane, and the properties of the resulting membrane are shown in Tables 2 and 3.
[0119] [Table 2]
[0120] [Table 3]
[0121] The polyamide films of Examples 1-6 and 9 exhibit particularly excellent flexural strength and transparency, and also very excellent visibility. The polyamide films of Examples 7, 8, 10, and 13 exhibit excellent flexural strength and transparency, and excellent visibility. The polyamide films of Examples 11 and 12 exhibit excellent flexural strength.
[0122] On the other hand, the polyamide films of Comparative Examples 1-3 had poor bending resistance because the stretching conditions were inappropriate, resulting in a smaller difference between the refractive index in the MD direction and the refractive index in the TD direction. Additionally, the polyester film of Comparative Example 4 was formed from polyethylene terephthalate, and therefore also had poor bending resistance.
Claims
1. A polyamide film, characterized in that, Contains semi-aromatic polyamides, The polyamide film has a refractive index of less than 1.600 in the length direction and / or width direction, and the difference between the refractive index in the length direction and the refractive index in the width direction is greater than 0.
030.
2. The polyamide film according to claim 1, wherein, The 0.2% offset strain of the polyamide film in the length and / or width directions is greater than 2.30%.
3. The polyamide film according to claim 1, wherein, The haze of the polyamide film is below 1.0%.
4. The polyamide film according to claim 1, wherein, The total light transmittance of the polyamide film is above 85.0%.
5. The polyamide film according to claim 1, wherein, The polyamide film has a thickness of 100. μ Below m.
6. A laminated film, which is formed by laminating the polyamide film of any one of claims 1 to 5 with a hard coating layer.
7. A display, characterized in that, The polyamide film having any one of claims 1 to 5.
8. A display, characterized in that, Having the laminated film of claim 6, The display is configured with the hard coating of the laminated film on the outside.
9. A method for manufacturing the polyamide film according to any one of claims 1 to 5, characterized in that, Includes: a stretching process, wherein an unstretched film containing semi-aromatic polyamide is uniaxially stretched along the length or width direction at a stretching ratio of 1.5 to 4.0 times.
10. The method for manufacturing a polyamide film according to claim 9, wherein, No heat-fixing or relaxation treatment is performed after the stretching process.
11. The method for manufacturing a polyamide film according to claim 9, wherein, The heat of crystallization of the unstretched membrane is above 20 J / g.
Citation Information
Patent Citations
Polyester film and application of the same
JP2023061931A